Effect of Nutrition Education Using PowerPoint and Crossword Puzzles on Healthy Snacks on Knowledge, Attitudes, and Macronutrient Intake of Elementary School Students - Angela Chandra Deswita; Hidayatusy Syukrina Puteri; Ajib Jayadi (Jurnal Kesehatan Cendikia Jenius, 2025)
Nutritional problems among school-age children in Indonesia remain a serious concern, with a stunting prevalence of 15.2%, wasting 6.3%, and obesity 5.3%. Consumption of unhealthy snacks contributes to an imbalance in macronutrient intake. The aim of this activity was to analyze the effect of nutrition education using PowerPoint and crossword puzzle media on students’ knowledge, attitudes, and macronutrient intake. A pre-experimental study with a one-group pretest-posttest design involved 41 fourth- and fifth-grade students at SD Negeri 1 Sri Katon. Data were collected using knowledge and attitude questionnaires and a 2×24-hour food recall. The study showed a significant increase in knowledge scores from 51.46 to 83.66 (p<0.001), an increase in supportive attitudes from 29.3% to 63.4% (p<0.001), and improvements in the adequacy of carbohydrate, protein, and fat intake (p<0.001). Conclusion: Nutrition education using interactive media effectively improved elementary school students’ knowledge, attitudes, and macronutrient intake. It is recommended to implement interactive nutrition education in elementary schools regularly to enhance knowledge, attitudes, and healthy consumption behaviors.